Modified Kuppuswamy socioeconomic scale updated for the year 2025 - Shah, Pappu P.; Singh, Mongjam M. (International Journal Of Community Medicine And Public Health, 2025)
Socio economic status (SES) is one of the most crucial determinants of health outcomes. It is an intricate construct encompassing an individual’s or family’s economic and social standing relative to others in the society. It is a composite indicator where matrices like income, education, occupation wealth (assets and capitals) and other related variables are mainly taken into consideration. It is pertinent to note that SES has profound influence on health, affordability and accessibility to healthcare and overall well-being of the individual and the family. It has been shown that people from poor socio-economic status have poor housing conditions, less education, limited job opportunities and consequent outcomes such as poor health conditions. On the contrary, people of higher socio-economic status enjoy the privilege of higher education, nutritious food, good housing, good job opportunities and better access to health care services leading to a long and healthy life.